Acculturation of sharia and custom in the ban on single organs - Siti Nurhafiza; Zufriani Zufriani; Maryani Maryani (Asian Journal of Islamic Studies and Society, 2024)
his study examines how Islamic (sharia) values and local customary law (adat) have come together in the customary prohibition of single-organ (orgen tunggal) entertainment in Koto Petai Village, Kerinci Regency, Jambi. Orgen tunggal refers to solo electronic-keyboard performances that are inexpensive to stage and, in this community, are associated with late-night crowds, alcohol, and brawls. Customary leaders (ninik mamak) have enforced the ban since 2003. Rather than asking whether the prohibition is justified, the study asks how villagers understand, justify, comply with, and at times question it, and what the case reveals about the workings of communal customary law. The research used a qualitative case study with a phenomenological orientation. Data were generated through in-depth semi-structured interviews with purposively selected participants customary leaders, a religious leader, a village official, and ordinary villagers alongside non-participant observation and review of relevant local materials during 2024. Interview transcripts were analysed thematically with the support of NVivo 12, and trustworthiness was strengthened through source and method triangulation, member checking, and an audit trail. Five themes were constructed: a religious moral order as the ground of the ban; the fusion of sharia and adat into a single unwritten norm; customary social control through deliberation (musyawarah) and graduated sanctions; broad compliance accompanied by quieter negotiation and differing views; and communal customary law as a living, binding order. The case suggests that acculturation here is less a finished state of harmony than an ongoing negotiation in which religious and customary authority reinforce one another while still leaving room for differing community voices.